Thomas J. Catlaw, Fabricating The People: Politics and Administration in The Biopolitical State - Prasetyo, Antonius Galih (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2012)
Book Review (Alamaba: The University of Alamaba Press, 2007, 258 hal)